Analýza zadluženosti domácností - Černohorská, Liběna; Linhartová, Veronika (Univerzita Pardubice, 2011)
Debts are currently troubling many households. They often try to solve it by obtaining another loan, which ufortunately doesn´t solve their problem. Household indebtedness is continuously growing and households aren´t able to create their own savings. This paper focuses on on the development of Czech household indebtedness, its current status and anticipated future development. This topic will be analysed not just in general point of view, but also in terms of income and age.
Keywords: indebtedness; household; bank loans; bank deposits; savings